2020
DOI: 10.1096/fj.201902583r
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal upregulation of hypoxia‐inducible factor‐1α and persistently enhanced placental adenosine signaling contribute to the pathogenesis of preeclampsia

Abstract: Recent evidence indicates that elevated placental adenosine signaling contributes to preeclampsia (PE). However, the molecular basis for the chronically enhanced placental adenosine signaling in PE remains unclear. Here, we report that hypoxia‐inducible factor‐1α (HIF‐1α) is crucial for the enhancement of placental adenosine signaling. Utilizing a pharmacologic approach to reduce placental adenosine levels, we found that enhanced adenosine underlies increased placental HIF‐1α in an angiotensin receptor type 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…Intriguingly, a previous study conducted using a mouse model of PE induced by administration of LIGHT reported excessive accumulation of adenosine in the placenta. 44 Extracellular adenosine production activates the NLRP3 inflammasome via ADORA2A and ADORA2B in inflammatory cells, such as macrophages, and functions as a key regulator of inflammation. 45,46 Since the enhancement of inflammation in the placenta, which is induced by the damage-associated molecular patterns (DAMPs)-associated NLRP3 inflammasome activation, reportedly plays an important role in the pathophysiology of PE, 47 adenosine signaling might be involved in this inflammatory pathway.…”
Section: Adenosine and Aberrant Immunological State Related To Pementioning
confidence: 99%
See 3 more Smart Citations
“…Intriguingly, a previous study conducted using a mouse model of PE induced by administration of LIGHT reported excessive accumulation of adenosine in the placenta. 44 Extracellular adenosine production activates the NLRP3 inflammasome via ADORA2A and ADORA2B in inflammatory cells, such as macrophages, and functions as a key regulator of inflammation. 45,46 Since the enhancement of inflammation in the placenta, which is induced by the damage-associated molecular patterns (DAMPs)-associated NLRP3 inflammasome activation, reportedly plays an important role in the pathophysiology of PE, 47 adenosine signaling might be involved in this inflammatory pathway.…”
Section: Adenosine and Aberrant Immunological State Related To Pementioning
confidence: 99%
“…A study conducted using a mouse model of PE induced by the administration of human AT 1 -AA to pregnant mice reported that enhanced placental adenosine signaling via ADORA2B plays an important role in the pathogenesis of PE. 33,44 AT1-AA-induced excessive accumulation of adenosine in the mouse placenta is mediated by placental CD73. By integrating previous fragmentary findings on aberrances in inflammation and immune system, adenosine signaling is anticipated to be the key pathway in understanding the whole aspect of PE pathogenesis.…”
Section: Adenosine and Aberrant Immunological State Related To Pementioning
confidence: 99%
See 2 more Smart Citations
“…2 Placenta may play a major role in its pathogenesis. 3 The pathological manifestations of placenta in patients with PE are shallow placental implantation, small villi area, and poorly developed blood vessels in the villi. 4 The degradation of extracellular matrix (ECM) is a key part of trophoblast invasion.…”
Section: Introductionmentioning
confidence: 99%